Analisis Penggunaan Payback Periode, Average Rate of Return, Benefit Cost-Ratio, dan Break Even Point dalam Menilai Kelayakan Usaha Mikro Kecil dan Menengah - Legowo Wati, Tri; Hendri, Nedi; Nusantoro, Jawoto (Universitas Muhammadiyah Metro, 2025)
This study assesses the feasibility of micro, small, and medium enterprises (MSMEs) in straw mushroom cultivation in Bantul using four financial analysis methods: Payback Period, Average Rate of Return (ARR), Benefit-Cost Ratio (B/C Ratio), and Break-Even Point (BEP). The descriptive qualitative research method was used because the research was conducted in natural conditions (natural setting). Overall, the results of the analysis indicate that the straw mushroom cultivation business in Bantul, especially the PKUR Mushroom Merang, is feasible to be continued and developed. This business provides a quick return on investment, adequate profits, controlled risks, and high profit potential. These findings can be a reference for entrepreneurs and investors who are interested in the straw mushroom cultivation sector and provide a positive contribution to the local economy in Bantul.